2012
DOI: 10.1007/s11999-012-2499-9
|View full text |Cite
|
Sign up to set email alerts
|

Save the Torn Labrum in Hips With Borderline Acetabular Coverage

Abstract: Background Hip arthroscopy for labral tears improves short-term function, but reoperations occur in 5% to 47% of patients. The effect of borderline acetabular coverage on reoperation rate has been debated. Labral repair rather than débridement has been proposed to improve function, but the effect on reoperation rate is unclear. Questions/Purposes We determined whether (1) borderline compared to adequate acetabular coverage increased reoperations and (2) labral repair compared to débridement reduced reoperation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
92
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 32 publications
0
92
0
Order By: Relevance
“…A couple of studies have been published looking specifically at the results of surgical treatment of borderline dysplastic hips, with one study showing higher rates of failure in the borderline hips than in those with adequate acetabular cover [10], and the other study showing comparable outcomes [15]. Currently stability of the hip is assessed with the LCEA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A couple of studies have been published looking specifically at the results of surgical treatment of borderline dysplastic hips, with one study showing higher rates of failure in the borderline hips than in those with adequate acetabular cover [10], and the other study showing comparable outcomes [15]. Currently stability of the hip is assessed with the LCEA.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of the FEAR index to identify instability was less encouraging and this may reflect other factors such as ligamentous laxity being pertinent in the decision-making process. Interestingly, hypermobility has been noted to be more prevalent in symptomatic patients with FAI [10,14].…”
Section: Discussionmentioning
confidence: 99%
“…A surgeon also has the option of repair, reconstruction, or resection when the labrum is detached for rim resection. Several clinical studies suggest that patients with repairs fare better than those with excision [20,22,31,[35][36][37]51], but another study found that the labrum is repaired in only one-fourth of arthroscopic…”
Section: Background Rationale and Study Findingsmentioning
confidence: 99%
“…Animal and clinical studies suggest that repairs can heal [6,48] and that patients with repairs enjoy better function when compared with those with excision [21,22,31,36,51]. In cases in which the labrum cannot be repaired as a result of complete ossification, prior resection, radial discontinuity, or poor tissue quality, techniques for labral reconstruction using an iliotibial band, ligamentum teres, or allograft tissue have been described by experienced surgeons treating younger patients with large labral defects [20,26,52,55].…”
Section: Introductionmentioning
confidence: 99%
“…There is increased recognition of coexisting impingement and dysplasia, underscoring the importance of accurate preoperative assessment of morphology and hip pathomechanics. The challenging patient with so-called borderline acetabular dysplasia (lateral center-edge angle of 20°-25°) is increasingly recognized, as is the importance of preserving the labrum in these patients [7]. Studies of periacetabular osteotomy and rotational osteotomy from Europe, North America, and Japan consistently show relief of pain and restoration of function, provided strict patient selection criteria are met [15].…”
mentioning
confidence: 99%